Kajian Manajemen Risiko Pada Proyek Preservasi Jalan Dengan Metode AHP (Analytical Hierarchy Process) - Yongky Togelang; Fabian J. Manoppo; Ariestides K. Torry Dundu (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This study aims to conduct a risk management study on the Poigar-Kaiya-Maelang Road Preservation project that affects the achievement of project performance on time by identifying, classifying, analyzing, handling dominant risks. The research method used is descriptive qualitative analysis method to identify and classify dominant risks. The variables used are literature studies, expert validation and factor analysis and main component analysis using SPSS version 26 program and quantitative descriptive analysis methods to get perceptions about the frequency and impact of risk on project time performance with risk management standards AS/ZNS 4360 :2004 and determining the priority scale for handling using the AHP method. The results showed that the dominant risks with significant risk categories (significant risk) with the AHP method obtained a priority scale for handling, namely planning and nature by 22.7%, resources and OHS 18.70%, personnel and equipment control by 14.5%. , productivity and distribution of materials by 12.8%, scheduling and finance by 11.3%, coordination and management by 8.2%, communication and work methods by 6.8%, operator capability by 4.9%.